2018
DOI: 10.1111/nhs.12580
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing sexual risk behaviors among adolescents: A community‐based participatory study

Abstract: Pregnancy rates and unprotected sex among Thai adolescents continue to increase. The aim of this community‐based participatory study was to identify gender differences in sexual behaviors and sexual risk factors, and to examine factors associated with sexual risk behaviors among 397 adolescents in northern Thailand. Twenty two community researchers facilitated the data collection by using smart phones or tablet computers on a privacy basis. Ordinal and logistic regressions identified predictors influencing pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 24 publications
3
26
0
Order By: Relevance
“…34 More attention should be paid to this phenomenon, especially in the context of China, where there is not enough formal and comprehensive sexual education and counseling for adolescents. Similar to previous findings, 19,35 our study also revealed the gender differences in terms of early sexual debut and having multiple sexual partners, indicating that male students are more likely to engage in risky sexual behavior than female students.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…34 More attention should be paid to this phenomenon, especially in the context of China, where there is not enough formal and comprehensive sexual education and counseling for adolescents. Similar to previous findings, 19,35 our study also revealed the gender differences in terms of early sexual debut and having multiple sexual partners, indicating that male students are more likely to engage in risky sexual behavior than female students.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous researches, 5,10 the findings of our study confirmed that the proportion of male sexual minorities was lower than female sexual minorities, which could be explained by gender inequality caused by cultural factors, gender roles, and power differences in gender relations. 28,29 The results showed that China's college students have a lower proportion of early sexual debut compared with other studies, 30 which may indicate the relatively conservative attitude towards sex among Chinese college students 31 However, a considerable number of Chinese students have sexual debut at an early age, which may bring negative health consequences to them, including unplanned pregnancy and sexually transmitted infections. 32 Consistent with previous researches, 22,33 our findings showed that college students tended to have multiple sexual partners, which is a great risk factor for HIV/STD infection.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Self-efficacy to refuse sex is a strong protective factor against unwanted sexual activity and is a modifiable mediator between prior SV and risky sexual behaviors [ 28 ]. Self-efficacy to refuse sex includes maintaining the confidence and intention to refuse unwanted sexual encounters [ 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pregnancy in adolescence is a public health problem worldwide and nationally (Azevedo et al, 2015;Sama et al, 2017;Settheekul et al, 2019). For this reason, a specific target of the sustainable development goals (SDGs) is that by 2030, adolescents will have universal access to sexual and reproductive health services (Mehra et al, 2018;World Health Organization, 2017).…”
Section: Introductionmentioning
confidence: 99%